2022
DOI: 10.1111/acer.14945
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prenatal alcohol and/or tobacco exposure on brain structure in a large sample of children from a South African birth cohort

Abstract: Background Neuroimaging studies have emphasized the impact of prenatal alcohol exposure (PAE) on brain development, traditionally in heavily exposed participants. However, less is known about how naturally occurring community patterns of PAE (including light to moderate exposure) affect brain development, particularly in consideration of commonly occurring concurrent impacts of prenatal tobacco exposure (PTE). Methods Three hundred thirty‐two children (ages 8 to 12) living in South Africa's Cape Flats township… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…These functional correlates of lateral orbitofrontal cortex and nucleus accumbens are consistent with the negative association between PTE and global cognition in children between 9 to 12 years old found in the current literature, suggesting a potential brain-behavior relationship ( Fried et al, 1998 ; Gonzalez et al, 2023 ). Our results are consistent with prior studies from this same birth cohort representing community patterns of PAE and PTE, showing more widespread cortical and subcortical brain alterations with PTE compared to PAE at ages 6 years old ( Uban et al, 2023 ) and ages 8–12 years ( Marshall et al, 2022 ). Compared to alcohol, tobacco use is less likely to be cut back during pregnancy and more likely to be associated with tobacco exposure after pregnancy ( Leech et al, 1999 ; Cornelius and Day, 2000 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These functional correlates of lateral orbitofrontal cortex and nucleus accumbens are consistent with the negative association between PTE and global cognition in children between 9 to 12 years old found in the current literature, suggesting a potential brain-behavior relationship ( Fried et al, 1998 ; Gonzalez et al, 2023 ). Our results are consistent with prior studies from this same birth cohort representing community patterns of PAE and PTE, showing more widespread cortical and subcortical brain alterations with PTE compared to PAE at ages 6 years old ( Uban et al, 2023 ) and ages 8–12 years ( Marshall et al, 2022 ). Compared to alcohol, tobacco use is less likely to be cut back during pregnancy and more likely to be associated with tobacco exposure after pregnancy ( Leech et al, 1999 ; Cornelius and Day, 2000 ).…”
Section: Discussionsupporting
confidence: 92%
“…The potential for PTE from others’ use may be a mechanism for reaching higher doses of exposure, and/or longer durations of exposure across postnatal developmental stages, unlike PAE. Together, these mechanisms for PTE that are unique from those of PAE may explain the more widespread effects on brain development at ages 6 ( Uban et al, 2023 ) and 8–11 years as seen here and in Marshall et al (2022) . Interestingly, PTE dose-response relationships did not show significant results after corrections for multiple comparisons ( Marshall et al, 2022 ), suggesting that PTE exposure from the postnatal period, or relating to perinatal tobacco exposure from others around the pregnant person or baby may be driving PTE outcomes more than maternal use in pregnancy alone.…”
Section: Discussionmentioning
confidence: 77%
“…Magnetic resonance imaging (MRI) studies of individuals with PAE have identified structural changes in brain size and shape (including microcephaly), gray and white matter volumes, cortical thickness (CT), and surface area (SA) in children, adolescents, and young adults ( Sowell et al, 2002b ; Riley et al, 2004 ; Lebel et al, 2011 ; Zhou et al, 2011 ; Roussotte et al, 2012 ; Yang et al, 2012a ). While the severity of abnormalities is positively correlated with higher doses of PAE ( Sowell et al, 2008 ; Zhou et al, 2011 ; Hoyme et al, 2016 ; Marshall et al, 2022 ), some studies found teratogenic effects due to PAE even in cases of minimal alcohol consumption in humans ( Joseph et al, 2014 ; Williams and Smith, 2015 ; Marshall et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize the structural and cultural factors, including historical sociopolitical frameworks, which might contribute to the high prevalence of PAE present in certain South African communities. The colonial apartheid regime in South Africa created a system of significant economic and sociopolitical inequalities that served to disadvantage communities such as those in the current study sample (Adebiyi et al, 2021; Jacobson et al, 2017; Marshall et al, 2022; May et al, 2019). Additionally, in health systems with access to limited resources, more acutely life-threatening medical conditions may be prioritized over conditions that are more chronic and less immediately life-threatening, leading to less resource allocation to mental health and substance use disorder treatment and support (Williams & Wyatt, 2015).…”
Section: Contextualizing Pae In South African Communitiesmentioning
confidence: 99%